Root hairs explain P uptake efficiency of soybean genotypes grown in a Pdeficient Ferralsol - Vandamme, Elke; Renkens, M.; Pypers, Pieter; Smolders, E.; Vanlauwe, Bernard; Merckx, Roel (Springer, 2013)
Background and aims Incorporating soybean (Glycine max) genotypes with a high nitrogen fixation potential into cropping systems can sustainably improve the livelihoods of smallholder farmers in Western Kenya. Nitrogen fixation is, however, often constrained by low phosphorus (P) availability. The selection of soybean genotypes for increased P efficiency could help to overcome this problem. This study investigated the contribution of different root traits to variation in P efficiency among soybean genotypes. Methods Eight genotypes were grown in a Ferralsol amended with suboptimal (low P) and optimal (high P) amounts of soluble P. Root hair growth was visualized by growing plants in a novel agar system where P intensity was buffered by Al2O3 nanoparticles. Results In the pot trial, P uptake was unaffected among the genotypes at high P but differed about 2-fold at low P. The genotypes differed in P uptake efficiency but not in P utilization efficiency. Regression analysis and mechanistic modeling indicated that P uptake efficiencies were to a large extent related to root hair development (length and density) and, to a lower extent, to colonization by mycorrhizal fungi. Conclusion Breeding for improved root hair development is a promising way to increase P uptake efficiency in soybean.